Design and development of motored engine for two-stroke spark ignition (SI) engine - Mohd Fikri Azri, Mat Saad (2008)
The two stroke engines have been around for more than a century and have survived so far, primarily in portable applications. From the beginning, two stroke engines have suffered from poor fuel economy and high fuel emissions compared to the larger, heavier, but more efficient than four stroke design. The scavenging process in the two-stroke engine has direct influence on engine performance on their combustion process and remains one of the important strategies towards improvement of fuel efficiency and reduction of pollutant. The new of engine test rig was design and fabricate for motoring concept a single cylinder 30.5 cc two strokes spark-ignition. Then measurement installation was done to the test engine. It will be the platform for further study in investigation the in-cylinder characteristic whiles the scavenging process for motored condition. The result of this project is a new engine test rig with motored condition for two-stroke spark ignition (SI) engine with instrument installation for data measurement.